The Effect of Sport Massage on Anxiety Before facing Exhibition - Ading Mulyadi; Sartono Sartono (Journal of Physical Education and Sport Science, 2019)
The purpose of this research is to find out: The Effect of Sport Massage on Anxiety Before Facing Match Test on Athletes Pencak Silat STKIP Muhammadiyah Kuningan Facing Match Test. This research method is an experimental method with one-group pretest-postest design research design. The population of this study was 25 athletes. Sample Determination using purposive sampling technique used by 15 athletes Pencak Silat STKIP Muhammadiyah Kuningan.. The results of analysis and processing of pre test data obtained the lowest score of 7,highest score of 23, obtained an average of 15.86 including mild anxiety with a distance of 14 - 20 While post test data obtained the lowest score 2, highest score of 20, and obtained an average score of 7.5 including no anxiety with a distance of less than 14. There was a decrease in anxiety before the test. Based on testing shows that both distribution tests are normal. Therefore to test the hypothesis using paired samples t-test the pre test and post test values show the t-count value for sports massage treatment is 7,515> t-table 1,753 with a probability (sig.) 0.00 probability value (sig.) of 0.00 < 0.05. there aresignificant differences. So H0 was rejected and Ha was accepted.